Cortisol Levels during the Menopausal Transition and Early Postmenopause: Observations from the Seattle Midlife Women’s Health Study - Woods, Nancy Fugate (2009)
AIMS: Cortisol levels rise among some women during the late stage of the menopausal transition, but we know little about changes in cortisol levels in relation to menopause-related factors (menopausal transition (MT) stage, urinary estrone glucuronide, testosterone, FSH), stress-related factors (epinephrine, norepinephrine, perceived stress), symptoms (hot flashes, mood, memory and sleep), social factors (income adequacy, role burden, social support, employment, parenting, and history of sexual abuse) and health-related factors (depressed mood, perceived health, physical appraisal, BMI, and smoking). Aims were to examine the influence of menopause-related factors, stress-related factors, symptoms, social, and health-related factors on cortisol levels during the menopausal transition. METHODS: A subset of Seattle Midlife Women’s Health Study participants who provided data during the late reproductive, early and late MT stages or early postmenopause (PM) and who were not using hormone therapy or corticosteroids (N=132 women, up to 5218 observations) including menstrual calendars for staging the MT, annual health reports, health diaries, and overnight urine specimens (assayed for cortisol, catecholamines, estrone glucuronide and FSH) between 1990 and 2005 were included. Perceived stress, symptoms, and health behaviors were assessed in a health diary. Health-related and social factors were assessed in an annual health update. Multilevel modeling was used to test effects of menopause- related and other factors on overnight cortisol levels. RESULTS: When tested with age as a measure of time, menopause-related covariates, including estrone glucuronide (E1G), FSH, and testosterone were associated with significant increases in overnight cortisol levels (p<.0001). Likewise, epinephrine and norepinephrine were each associated significantly with overnight cortisol levels (p<.0001). In multivariate analyses, E1G, FSH, and testosterone constituted the best set of predictors. CONCLUSIONS: Overnight cortisol levels during the MT were associated with E1G, testosterone, and FSH levels. In addition, they were significantly and positively associated with epinephrine and norepinephrine. MT stage, symptoms, and social, stress-related, and health-related factors had little relationship to overnight cortisol levels when other biological indicators were considered.